Analysis of the Influence of Education Level, JPM, and Female Labor on Economic Growth in 10 Provinces of Sumatera Island in the Islamic Economy from 2013 to 2023 - Azzahra, Andini Dwi; Putri, Rosydalina; Utamie, Zathu Restie (Jurnal Iqtisaduna, 2025)
This study aims to influence the Level of Education, the Number of Poor Population and the Female Workforce on Economic Growth in 10 Provinces of Sumatra Island from 2013-2023. This study uses a quantitative approach with a panel data analysis method. Data was obtained through the Central Bureau of Statistics. The F test has a value of 0.000000. The results of this study indicate that the Level of Education and the Female Workforce have a positive and significant effect on Economic Growth, while the Number of Poor Population harms Economic Growth.